Comparison of Olympic systems in China and UK in elite sport - Li, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introductions China and the UK will host the Olympic Games in 2008 and 2012, respectively. Comparison of the two countries preparations and management towards the games has shown certain strengths and weaknesses. This study aims to improve China's sports management and its operation in sport economy. Methods By means of SWOT analysis, this paper compares the figures between the Chinese and the British Olympic system situations, analyzing both countries` strengths and weaknesses. Results The two countries` sports systems are described through the history of involvement with the Olympic Games and the medals won by the two countries in recent Summer Games. Analysis of the strength and weakness of the "National Centralized System" of China and the less centralized state system of the UK is also given. China's strength is that the government increases its investment in sports to promote sports development and to enhance China's international status. The weakness is that its investment relies primarily upon the government, making sustainability difficult. For the UK, its strength is market and commercial operation, which offers the basic mechanism for sustainable development. These multi-channel sources of funds, thereby, reduce the financial burden upon state and local government. Its weakness is that government will face the pressure of input for the Olympic Games. Conclusions From the British sports system and its economic mode of operation, the following reference would be valuable for China: 1. The operation of the market mechanism ensures a sustainable development of sports. 2. The whole nation`s strong sports concepts and people`s broad participation form a solid national population foundation for sport.